Control of Neurotransmitter Release by Presynaptic Waveform at the Granule Cell to Purkinje Cell Synapse - Sabatini, Bernardo L. (J Neurosci, 1997)
The effect of changes in the shape of the presynaptic action potential on neurotransmission was examined at synapses between granule and Purkinje cells in slices from the rat cerebellum. Low concentrations of tetraethylammonium were used to broaden the presynaptic action potential. The presynaptic waveform was monitored with voltage-sensitive dyes, the time course and amplitude of presynaptic calcium entry were determined with fluorescent calcium indicators, and EPSCs were measured with a whole-cell voltage clamp. Spike broadening increased calcium influx primarily by prolonging calcium entry without greatly affecting peak presynaptic calcium currents, indicating that the majority of calcium channels reach maximal probability of opening in response to a single action potential and that spike broadening increases the open time of these channels. EPSCs were exquisitely sensitive to elevations of calcium influx produced by spike broadening; there was a high power relationship between calcium influx and release such that a 23% increase in spike width led to a 25% increase in total calcium influx, which in turn doubled synaptic strength. The finding that even small changes in spike width influence neurotransmitter release suggests that altering the presynaptic waveform may be an important means of modifying the strength of this synapse. Waveform changes do not, however, contribute significantly to presynaptic modulation via activation of adenosine A(1) or GABA(B) receptors. Furthermore, greatly reducing presynaptic calcium influx did not alter the presynaptic waveform, indicating that calcium channels and calcium-activated channels do not participate in shaping the presynaptic waveform.